The laughing mask - Aguiar, Michael; Jenkings, Jeff; Hardy, John (Actor); Rivers, Sheyenne; Lee, Gabriel (Pendragon Pictures, 2014)
A grisly murder perpetrated by a deranged killer, Jake Johnson's wife and daughter were murdered by a Psychotic vigilante only known as The Laughing Mask. As the police look for clues and the body count begins to rise, Johnson will play a dangerous game in order to avenge his family's death.